Magnetic resonance elastography resolving all gross anatomical segments of the kidney during controlled hydration - Wolf, Marcos; Darwish, Omar; Neji, Radhouene; Eder, Michael; Sunder-Plassmann, Gere; Heinz, Gertraud; Robinson, Simon Daniel; Schmid, Albrecht Ingo; Moser, Ewald V.; Sinkus, Ralph; Meyerspeer, Martin (Frontiers in Physiology, 2024)
Introduction: Magnetic resonance elastography (MRE) is a non-invasive method to quantify biomechanical properties of human tissues. It has potential in diagnosis and monitoring of kidney disease, if established in clinical practice. The interplay of flow and volume changes in renal vessels, tubule, urinary collection system and interstitium is complex, but physiological ranges of in-vivo viscoelastic properties during fasting and hydration have never been investigated in all gross anatomical segments simultaneously. Method: Ten healthy volunteers underwent two imaging sessions, one following a 12-hour fasting period and the second after a drinking challenge of >10mL per kg body weight (60 to 75 min before the second examination). High-resolution renal MRE was performed using a novel driver with rotating eccentric mass placed at the posterior-lateral wall to couple waves (50 Hz) to the kidney. The biomechanical parameters, shear wave speed (cs in m/s), storage modulus (Gd in kPa), loss modulus (Gl in kPa), phase angle (𝛶=2/𝜋 atan(𝐺𝑙/𝐺𝑑)) and attenuation (α in 1/mm) were derived. Accurate separation of gross anatomical segments was applied in post-processing (whole kidney, cortex, medulla, sinus, vessel). Results: High-quality shear waves coupled into all gross anatomical segments of the kidney (mean shear wave displacement: 163±47 µm, mean contamination of 2nd upper harmonics <23 %, curl/divergence: 4.3±0.8). Regardless of the hydration state, median Gd of the cortex and medulla (0.68±0.11 kPa) was significantly higher than that of the sinus and vessels (0.48±0.06 kPa), and consistently, significant differences were found in cs, Υ, and Gl (all p<0.001). The viscoelastic parameters of cortex and medulla were not significantly different. After hydration sinus exhibited a small but significant reduction in median Gd by -0.02±0.04 kPa (p=0.01), and, consequently, the cortico-sinusoidal-difference in Gd increased by 0.04±0.07 kPa (p=0.05). Only upon hydration, the attenuation in vessels became lower (0.084±0.013 1/mm) and differed significantly from the whole kidney (0.095±0.007 1/mm, p=0.01). Conclusion: High-resolution renal MRE with an innovative driver and well-defined 3D segmentation can resolve all renal segments, especially when including the sinus in the analysis. Even after a prolonged hydration period the approach is sensitive to small hydration-related changes in the sinus and in the cortico-sinusoidal-difference.